2017
DOI: 10.1371/journal.pone.0166360
|View full text |Cite
|
Sign up to set email alerts
|

Leptin concentration and risk of coronary heart disease and stroke: A systematic review and meta-analysis

Abstract: Background and purposeAlthough high leptin concentration has been shown to be correlated with established vascular risk factors, epidemiologic studies have reported inconclusive results on the association between leptin and cardiovascular diseases (CVD). Therefore, a meta-analysis was performed to evaluate this issue.MethodsWe searched Pubmed, Embase, and the Cochrane Library from their inception to Jan 2016 for both case-control and cohort studies that assessed leptin concentration and CVD risk. Reports with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 42 publications
4
28
0
3
Order By: Relevance
“…In a meta-analysis that included 13 cohort and case-control studies, totaling 4257 CVD patients and 26,710 non-CVD controls, high leptin levels were not independently associated with CAD in women (odds ratio (OR) = 1.03; 95% CI = 0.86-1.23) and men (OR = 1.09; 95% CI = 0.95-1.26) or with stroke in women (OR = 1.13; 95% CI = 0.87-1.47) and men (OR = 0.80; 95% CI = 0.59-1.09) [113].…”
Section: Leptinmentioning
confidence: 99%
“…In a meta-analysis that included 13 cohort and case-control studies, totaling 4257 CVD patients and 26,710 non-CVD controls, high leptin levels were not independently associated with CAD in women (odds ratio (OR) = 1.03; 95% CI = 0.86-1.23) and men (OR = 1.09; 95% CI = 0.95-1.26) or with stroke in women (OR = 1.13; 95% CI = 0.87-1.47) and men (OR = 0.80; 95% CI = 0.59-1.09) [113].…”
Section: Leptinmentioning
confidence: 99%
“…Relative risk factors include hypertension, smoking, dyslipidemia, diabetes, being overweight, and obesity. The best known functions of LEP are appetite reduction, enhancement of energy expenditure, and regulation of lipid metabolism, all of which contribute to regulating obesity, an important CAD risk factor 8 . Certain levels of plasma or serum LEP can exert other physiological effects, such as enhancing endothelial cell oxidative stress, stimulating growth of vascular smooth muscle cells, inducing arterial vascular wall injury, stimulating formation of reactive oxygen species, and stimulating the renin-angiotensin-aldosterone system 17,18 All of these effects may influence development of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…An ample body of evidence from studies among different human populations has revealed that serum or plasma LEP levels correlate with CAD, suggesting that LEP/LEPR might be involved in CAD pathogenesis, and LEP/LEPR gene polymorphisms may influence the risk of CAD 7,8 . Studies to date of relationships between LEP/LEPR gene polymorphisms and CAD have produced varying results.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other studies have reported a vascular protective role of leptin against atherosclerosis in either overweight or obese humans or animals . Recently, a meta‐analysis involving 4257 participants with CVD and 26 710 controls showed that elevated leptin levels may not be associated with the risk of developing coronary heart disease and stroke in both men and women …”
Section: Introductionmentioning
confidence: 99%
“…13,14 Recently, a meta-analysis involving 4257 participants with CVD and 26 710 controls showed that elevated leptin levels may not be associated with the risk of developing coronary heart disease and stroke in both men and women. 15 Suggested concepts which may explain the disparity between the beneficial and detrimental effects of leptin include the widespread cardiovascular and dose-dependent effects of leptin, as well as the concept of selective leptin resistance. 16 It is currently unknown whether leptin plays a role during the early phases of atherosclerosis development in young adults in the absence of overt CVD.…”
Section: Introductionmentioning
confidence: 99%